The Effect of Ethanol Extract Concentration of Rapet Bark (Parameria laevigata (Juss.) Moldenke) in Feminine Hygiene Preparations on Antimicrobial Activity - Aries Koes Sundoro; Lutfhi Berlian Shandra; Erwin Indriyati; wulan kartika Sari; Ahmad Fuad Masduqi; Eka Susanti Hp (Media Farmasi Indonesia, 2025)
Rapet bark (Parameria laevigata (Juss.) Moldenke) is a natural material containing secondary metabolites that can be utilized as antimicrobial agents. This study aims to determine the effect of ethanol extract concentration of rapet bark in feminine hygiene formulations on the growth of Candida albicans and Staphylococcus aureus. The research employed an experimental method in the preparation of feminine hygiene products using ethanol extract of rapet bark at concentrations of FI (5%), FII (10%), and FIII (15%). The soap evaluation parameters included cycling test, organoleptic test, pH test, foam height test, irritation test, and antimicrobial activity test using the cylinder cup method with pour plate inoculation technique. The feminine hygiene formulations met the soap evaluation requirements, with antimicrobial activity against fungi of 11.53 ± 0.0354 (FII) and 12.55 ± 0.037 (FIII), and against bacteria of 11.29 ± 0.023 (FI), 12.56 ± 0.0444 (FII), and 15.11 ± 0.018 (FIII). Data analysis using one-way ANOVA showed a significance value (p < 0.05), indicating that each extract concentration differed significantly, thereby affecting the inhibition zone against fungi and bacteria.